2021
DOI: 10.1001/jamaophthalmol.2021.1088
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Assessments of a Series of Newborns Gestationally Exposed to Maternal COVID-19 Infection

Abstract: IMPORTANCE Congenital viral infections leading to ocular abnormalities are frequent and devastating. As ophthalmological manifestations of COVID-19 in newborns are still unknown, it is important to clarify if SARS-CoV-2 could be associated with ocular abnormalities.OBJECTIVE To determine whether exposure to SARS-CoV-2 is associated with outcomes in 4the eyes of newborns. DESIGN, SETTING, AND PARTICIPANTSThis case series enrolled newborns from April to November 2020 from 3 different maternity hospitals in São P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…A low incidence of COVID-19 infection was identified among babies in an uncontrolled case series of Brazilian newborns of women with COVID-19 infection, and none exhibited ocular abnormalities. 84 …”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
“…A low incidence of COVID-19 infection was identified among babies in an uncontrolled case series of Brazilian newborns of women with COVID-19 infection, and none exhibited ocular abnormalities. 84 …”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
“…7 The virus is primarily transmitted via respiratory droplets, 8 but rare cases of vertical transmission from pregnant mothers to their children have also been reported. 9 A systemic review found that 6.3% of babies born to mothers with COVID-19 tested positive for the infection at birth. 10…”
Section: Systemic Findings Covid-19 Transmission and Infectionmentioning
confidence: 99%
“… 55 In contrast, a study of 165 newborns exposed to SARS-CoV-2 in Brazil found that only 6 patients had polymerase chain reaction (PCR)-confirmed COVID-19, and none had vascular abnormalities that were attributed to SARS-CoV-2. 9 Some ocular findings in children with COVID-19 may be related to their underlying systemic health.…”
Section: Ocular Manifestations In Adults and Childrenmentioning
confidence: 99%
“…An uncontrolled case series of Brazilian newborns of mothers with COVID-19 infection showed that none of the babies with a COVID-19-positive PCR test had ocular manifestations [ 28 ]. However, while this particular report may refute the association between SARS-CoV-2 and ophthalmic manifestations, many other studies have reported this association.…”
Section: Resultsmentioning
confidence: 99%